2011
DOI: 10.1103/physrevd.84.123501
|View full text |Cite
|
Sign up to set email alerts
|

Notes on ghost dark energy

Abstract: We study a phenomenological dark energy model which is rooted in the Veneziano ghost of QCD. In this dark energy model, the energy density of dark energy is proportional to Hubble parameter and the proportional coefficient is of the order Λ 3 QCD , where Λ QCD is the mass scale of QCD. The universe has a de Sitter phase at late time and begins to accelerate at redshift around z acc ∼ 0.6. We also fit this model and give the constraints on model parameters, with current observational data including SnIa, BAO, C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
110
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 103 publications
(125 citation statements)
references
References 85 publications
(61 reference statements)
14
110
0
Order By: Relevance
“…• ω = −1.13 +0.13 −0.14 , (Planck+WP+SNLS) • ω = −1.084 ± 0.0063, (WMAP+eCMB+BAO+H 0 +SNe) In case of MGDE DE candidate, we set the model parameters following (Cai et al 2012) and show the variation of NEC and EoS parameter in Figure 11. It is found that ω lies in the range −6 × 10 −35 < 1 + ω < −1 representing the phantom era of the universe consistent with the recent observations (Ade et al 2013;Hinshaw et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…• ω = −1.13 +0.13 −0.14 , (Planck+WP+SNLS) • ω = −1.084 ± 0.0063, (WMAP+eCMB+BAO+H 0 +SNe) In case of MGDE DE candidate, we set the model parameters following (Cai et al 2012) and show the variation of NEC and EoS parameter in Figure 11. It is found that ω lies in the range −6 × 10 −35 < 1 + ω < −1 representing the phantom era of the universe consistent with the recent observations (Ade et al 2013;Hinshaw et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…We have selected two generalized form of GDE models, one suggested by GarciaSalcedo et al (2013) and other model is suggested by Cai et al (2012) named as MGDE. The f (T ) model corresponding to Garcia-Salcedo GDE is introduced in Eq.(18).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations